Nutrient Composition Analysis in Quasipaa spinosa Eggs - Han Li; Piao Zhu; Yibin Hu; Jianfeng Yuan; Gang Yang; Rongquan Zheng (Journal of Food Quality, 2025)
The objective of this study was to determine the nutrient composition of Quasipaa spinosa eggs and evaluate their nutritional value. The findings from this study can be utilized to propose recommendations for further development of Q. spinosa. The fatty acids, amino acids, mineral elements, crude fat, crude protein, and other nutrients in Q. spinosa eggs were analyzed using the Chinese national standard methods. The composition of Q. spinosa eggs included moisture (77.97 ± 3.99%), crude protein (16.90 ± 2.24%), crude fat (2.33 ± 0.17%), and ash (0.84 ± 0.05%). The analysis identified 23 distinct fatty acids, with polyunsaturated fatty acids comprising 68.22% of the total fatty acid content, including linoleic acid (C18:2n6c, LA), α-linolenic acid (C18:3n3, ALA), eicosapentaenoic acid (C20:5n3, EPA), and docosahexaenoic acid (C22:6n3, DHA). Eighteen amino acids were detected in the eggs, with the total amino acid content (on a dry weight basis) being 64.45 ± 2.49%, of which essential amino acids constituted 24.27 ± 0.80%. The amino acid score analysis showed that lysine had the highest score. Among the eight commonly observed mineral elements, phosphorus and calcium had the highest levels. The abundance of unsaturated fatty acids, essential amino acids, phosphorus, and calcium in Q. spinosa eggs highlights their significant nutritional value, suggesting promising prospects for consumption and further development.